An evaluation of praise as a reinforcer for preschoolers' behavior. Issue 1 (20th June 2019) - Senn, Laura Perry; Bayles, Makenzie W.; Bruzek, Jennifer L.
Abstract : Behavior analysts and educators often recommend using praise, particularly descriptive praise, despite mixed empirical findings to support this recommendation. We evaluated the effectiveness of praise as a reinforcer during a reinforcer assessment using known tasks with preschoolers in Experiment 1. Praise functioned as a reinforcer for 2 of 6 participants; the remaining 4 participants required additional reinforcers (edibles) to show a reinforcement effect. We then compared the effectiveness of descriptive versus general praise for acquisition of unknown tacts and assessed participants' preference for the different types of praise for 4 participants from Experiment 1. Results are discussed within the context of the importance of determining individual efficacy and preference for praise.